Clinical and epidemiological investigations of Orbivirus infections in domestic dogs (Canis lupus familiaris) - Fosgate, Geoffrey Theodore (University of Pretoria, 2024)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2023.